2002
DOI: 10.1081/clt-120006751
|View full text |Cite
|
Sign up to set email alerts
|

Poisons in the Air: A Cause of Chronic Disease in Children

Abstract: Children represent the largest subpopulation of those susceptible to the adverse effects of air pollution. Compared to adults, children express a greater vulnerability, which can be explained by differences in: the circumstances of exposure related to age, their activities, their child status, differences in lung anatomy and physiology, differences in the clinical expression of disease, and their organ maturity. Many factors have to be assessed in order to evaluate the severity of toxic exposures: pollutant so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 59 publications
0
35
0
1
Order By: Relevance
“…In seven studies a comparison using aggregated population data was carried out, four of them performed comparisons between the mortality rates among different geographical units and the other three are time series studies which evaluated the short term effect of the variations in the levels of air pollutants on the number of deaths at the earliest stages of life. Of the three studies with an individual basis, two have used a retrospective cohort design [7,39] and the other one, cases and controls [40].…”
Section: Intrauterine and Infant Mortalitymentioning
confidence: 99%
“…In seven studies a comparison using aggregated population data was carried out, four of them performed comparisons between the mortality rates among different geographical units and the other three are time series studies which evaluated the short term effect of the variations in the levels of air pollutants on the number of deaths at the earliest stages of life. Of the three studies with an individual basis, two have used a retrospective cohort design [7,39] and the other one, cases and controls [40].…”
Section: Intrauterine and Infant Mortalitymentioning
confidence: 99%
“…Certain diseases that appear later in childhood (e.g. respiratory illnesses such as asthma) have become an increasingly significant health problem (Leikauf et al 1995;Mannino, Homa, and Pertowski 1998;Mathieu-Nolf 2002. ) and some suggest that hazardous air pollutants (HAPs) or air toxics could be aggravating these conditions (Burg and Gist 1998;Leikauf et al 1995;Ware et al 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…C hildren constitute the largest part of the population that is susceptible to the adverse effects of air pollution. [1][2][3] This environmental hazard is associated with various health problems among children, 4 5 and with an increased infant mortality. 6 Specifically, nitrogen dioxide (NO 2 ), the focus of this study, has been shown to be associated with low birth weight 7 and respiratory difficulties among children, including the severity of virally induced asthma symptoms 8 and clinically significant deficiencies in lung function growth.…”
mentioning
confidence: 99%